The effect of holmium on microstructure and mechanical properties of light metal alloy - Ahmad, Rosli; Rashid, M. H. S.; Hasan, Sulaiman; Harun, Zawati; Yusof, M. S.; Hassan, Suhaimi; Rahman, M.M. (Multidisciplinary Review Journal, 2020)
The thesis project investigates the effect of Holmium addition on the microstructure and mechanical properties of cast ZRE1 magnesium alloy. In the advancement of automotive and aerospace industries, the next generation of light metal alloy is magnesium due to its manufacturing abilities and lightweight material. The main limitation of Mg alloys is the ability to improve its mechanical properties. Rare earth elements were used as alloying elements for improving the mechanical properties and producing a new Mg-RE alloy with modified structure and strength. In this studies, it demonstrates the addition of RE at specific amount, which could be considered as main alloy element that may lead to extend limitation of RE application. The amount of Holmium (Ho) at 0.2, 0.4 and 0.6 wt. % were added separately to ZRE1 magnesium alloy. The Optical Microsope, FESEM coupled with EDX, and XRD were used to investigate the microstructure and mechanical properties, including tensile and hardness tests. The results showed that the Ho content at 0.2wt. % increased the ultimate tensile strength and yield strength compared to others Ho composition. Finally, the hardness value was increased and the additive had a significant improvement of mechanical properties, thus the ZRE1 magnesium alloy has been improved with Holmium addition.